ANALISIS PEMBERIAN MP-ASI DINI TERHADAP STATUS GIZI BAYI - Agustin Agustin (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
Background: Toddlers are a nutritionally vulnerable age group who need more nutrition because they have less nutritional intake and are at risk of experiencing malnutrition. The practice factor of giving Complementary Foods for Breastfeeding greatly affects the nutritional status of babies in the future. Most of the causes of under-five mortality are related to malnutrition or malnutrition due to inappropriate complementary feeding during infancy, such as giving Complementary Foods for Breastfeeding too early or too late. This study was conducted to determine the relationship between early complementary feeding and the nutritional status of infants in the working area of the Motoboi Kecil Health Center.Methode: This study was conducted using a quantitative descriptive type with a cross-sectional research design. Data was collected by means of observation using a questionnaire. This research was carried out in the working area of the Motoboi Kecil Health Center Kotamobagu City from April to May 2020. The research sample was 42 people. Data analysis was carried out in the form of univariate and bivariate analysis using the Chi-Square test.Result: Early complementary feeding had no significant effect on the nutritional status of infants in the working area of the Motoboi Kecil Health Center, the results of statistical tests proved that the P-value was 0.95 <? (0.05) which means that there was no relationship. which is marked between early complementary feeding and the nutritional status of infants.Conclusion: Indirectly Complementary Foods for Breastfeeding in infants early can affect infant nutrition. Giving Complementary Foods for Breastfeeding to infants early does not have a direct significant impact or influence on their nutritional status. Mother's behavior, economic conditions, and the quality of environmental sanitation have a significant effect on the nutritional status of infants.Suggestion: complementary foods should be given to babies after 6 months of age, however, complementary foods at that age should be given gradually. It is hoped that for further studies to conduct studies related to maternal behavior, economic conditions, and the quality of environmental sanitation on the nutritional status of infants. Keywords: Complementary Foods For Breastfeeding, Baby Nutrition. ABSTRAK Latar Belakang: Balita merupakan kelompok usia rentan gizi yang membutuhkan lebih banyak gizi karena asupan nutrisinya lebih sedikit yang berisiko mengalami kekurangan gizi. Faktor praktik pemberian MP-ASI sangat mempengaruhi status gizi bayi di kemudian hari. Sebagian besar penyebab kematian balita terkait dengan malnutrisi atau malnutrisi akibat pemberian makanan pendamping ASI yang tidak tepat pada masa bayi, seperti pemberian MP-ASI terlalu dini atau terlambat.Tujuan Penelitian ini dilakukan untuk mengetahui hubungan pemberian MP-ASI dini dengan status gizi pada bayi di wilayah kerja Puskesmas Motoboi Kecil.Metode: Penelitian ini dilakukan dengan menggunakan jenis deskriptif kuantitatif dengan desain penelitian cross-sectional. Pengumpulan data dilakukan dengan cara observasional menggunakan alat bantu kuesioner. Penelitian ini dilaksanakan di wilayah kerja Puskesmas Motoboi Kecil Kota Kotamobagu pada bulan April sampai Mei 2020. Sampel penelitian sebanyak 42 orang. Analisis data dilakukan secara univariate dan bivariate menggunakan uji Chi-Square.Hasil: Pemberian MPASI dini tidak berpengaruh signifikan terhadap status gizi bayi di wilayah kerja Puskesmas Motoboi Kecil, hasil uji statistik membuktikan bahwa P-value 0,95<? (0,05) yang artinya ada tidak ada hubungan. yang ditandai antara pemberian MP-ASI dini dengan status gizi bayi.Kesimpulan: Secara tidak langsung MP-ASI Pada bayi secara dini dapat mempengaruhi gizi bayi. Pemberian MP-ASI kepada bayi secara dini tidak memberikan dampak atau pengaruh yang signifikan secara langsung terhadap status gizinya.Perilaku ibu, kondisi ekonomi, dan kualitas sanitasi lingkungan berpengaruh signifikan terhadap status Gizi bayi.Saran: MP-ASI sebaiknya diberikan kepada bayi setelah berusia lebih dari 6 bulan, namun pemberian MP-ASI di usia tersebut diberikan secara bertahap. Diharapkan untuk kajian selanjutnya melakukan kajian terkait perilaku ibu, kondisi ekonomi, dan kualitas sanitasi lingkungan terhadap status gizi bayi. Kata Kunci: Makanan Pendamping ASI, Gizi Bayi